Recent advances in efficient and scalable solar hydrogen production through water splitting - Yihao Zheng; Ming Ma; Huaiyu Shao (Carbon Neutrality, 2023)
Abstract Solar hydrogen production through water splitting is the most important and promising approach to obtaining green hydrogen energy. Although this technology developed rapidly in the last two decades, it is still a long way from true commercialization. In particular, the efficiency and scalability of solar hydrogen production have attracted extensive attention in the field of basic research. Currently, the three most studied routes for solar hydrogen production include photocatalytic (PC), photoelectrochemical (PEC), and photovoltaic-electrochemical (PV-EC) water splitting. In this review, we briefly introduce the motivation of developing green hydrogen energy, and then summarize the influential breakthroughs on efficiency and scalability for solar hydrogen production, especially those cases that are instructive to practical applications. Finally, we analyze the challenges facing the industrialization of hydrogen production from solar water splitting and provide insights for accelerating the transition from basic research to practical applications. Overall, this review can provide a meaningful reference for addressing the issues of efficiency improvement and scale expansion of solar hydrogen production, thereby promoting the innovation and growth of renewable hydrogen energy industry. Graphical Abstract